Aplicação dos modelos poro neutro e média geométrica na estimativa da condutividade hidráulica de um latossolo - Comiran, Gilberto (2006)
In this work, it is shown an application of a model to obtain the hydraulic conductivity of soils no saturated using concepts Fractal Geometry and the laws of Laplace and of Poiseuille. For the obtaining of the soil water retention curve it was used the camera of pressure of Richards and the experimental data of hydraulic conductivity in function of the soil water content were obtained through the Method of Hillel with the tensiometry use, according to a potency model. The equation van Genuchten with their parameters was used for the obtaining of the hydraulic conductivity. The application of the models of the Geometric Average and of the Neutral Pore suggested by Fuentes was shown simple and capable of predicting the hydraulic conductivity satisfactorily.